Evangelical Feminism A history - Cochran, Pamela (New York New York University Press, 2005)
This history of the evangelical feminist movement traces the emergence and theological development of biblical feminism within evangelical Christianity in the 70s.
Keywords: Bible -- Feminist criticism -- History. Bible. Bibel